Implications of falsification theory and the constructivism paradigm in the development of science education and learning - Megawati; Yasir Riady; Firman; Yundi Fitrah; Ade Kusmana (Mitra Palupi, 2023)
Background: Science learning holds paramount significance in the advancement of science and technology. Two pivotal theories, falsification theory and the constructivism paradigm, profoundly influence the landscape of science education. Purpose: The purpose of this study is to explore the impact of falsification theory and the constructivism paradigm on the development of science learning. Falsification theory, pioneered by Karl Popper, underscores the necessity of rigorous testing and validation of scientific hypotheses, forming the bedrock for the evolution of scientific knowledge. Conversely, the constructivism paradigm accentuates the active role individuals play in constructing knowledge, emphasizing a student-centered approach that involves collaborative learning, and problem-solving. Design and methods: In this study, we delve into the implications of falsification theory and the constructivism paradigm in shaping science education. Falsification theory advocates for empirical proof and stringent testing of scientific hypotheses, while the constructivism paradigm promotes active student involvement in building their comprehension of scientific concepts. The study investigates how the integration of these two approaches can foster robust science learning environments, encouraging critical thinking, exploration, and profound understanding. Results: The synthesis of falsification theory and the constructivism paradigm in science learning holds promise for cultivating a rich educational experience. By finding a delicate balance between rigorous empirical testing and providing opportunities for active student engagement, educators can create a profound and meaningful learning journey for students. This integrated approach not only instills an appreciation for the scientific method but also nurtures a deep understanding of science concepts, ultimately shaping students into critical thinkers with a genuine enthusiasm for scientific exploration.